A Study on Teachers’ Practices and Perceptions on the Integration of ICT in the Teaching of Vocational Subjects - Raman, Rakesh Kumar; Ravichandran, R. (JOURNAL OF INDIAN EDUCATION, 2026)
This study investigates the integration of Information and Communication Technology (ICT) in vocational education within government secondary schools across various regions of India. Using a mixed-methods approach, data were collected from teachers and students in selected vocational schools. The objectives include assessing ICT facilities’ availability, examining teachers’ ICT usage, exploring students’ engagement with ICT, and identifying challenges faced by teachers. Purposive sampling was employed to select schools, teachers, and students. Findings reveal varying levels of ICT infrastructure availability and usage among schools and participants. Challenges such as inadequate training and resource limitations hinder effective ICT integration. The study provides insights into the current state of ICT integration in vocational education, offering implications for policy and practice to enhance teaching and learning processes. It emphasises the importance of addressing barriers to maximise ICT’s potential in vocational education settings.